Preoperative Depression Screening in Patients with Distal Radius Fractures: An Evaluation of Its Modifiability on Outcomes for Patients with Depressive Disorder - Nian, Patrick P.; Gordon, Adam M.; Baidya, Joydeep; Miller, Chaim; Choueka, Jack (Journal of Wrist Surgery, 2023)
Background It is unclear whether nonpharmacologic intervention for depressive disorder (DD) in the preoperative period can prevent postoperative complications in hand surgery patients.Questions/Purpose The aims were to evaluate whether psychotherapy visits/depression screenings within 90 days of open reduction and internal fixation (ORIF) for distal radius fractures (DRFs) were associated with lower rates of (1) medical complications and (2) health care utilization (emergency department [ED] visits and readmissions).Methods A retrospective analysis of an administrative claims database from 2010 to 2021 was performed. DD patients who underwent ORIF for DRF were 1:5 propensity score matched by comorbidities, including those who did (n = 8,993) and did not (n = 44,503) attend a psychotherapy visit/depression screening 90 days before surgery. Multivariate logistic regression models were constructed to compare the odds ratio (OR) of medical complications, ED visits, and readmissions within 90 days. The p-values less than 0.001 were significant.Results DD patients who did not attend a preoperative psychotherapy visit/depression screening experienced fivefold higher odds of total medical complications (25.66 vs. 5.27%; OR: 5.25, p < 0.0001), including surgical site infections (1.23 vs. 0.14%; OR: 8.71, p < 0.0001), deep wound infections (0.98 vs. 0.17%; OR: 6.00, p < 0.0001), and transfusions (1.64 vs. 0.22%; OR: 7.61, p < 0.0001). Those who did not attend a psychotherapy visit/depression screening experienced higher odds of ED utilizations (9.71 vs. 2.71%; OR: 3.87, p < 0.0001), however, no difference in readmissions (3.40 vs. 3.54%; OR: 0.96, p = 0.569).Conclusion Depression screening may be a helpful preoperative intervention to optimize patients with DD undergoing hand surgery to minimize postoperative complications and health care utilization.Level of Evidence Level III.
Keywords: psychotherapy; screening; depression; depressive disorder; open reduction and internal fixation; distal radius fracture; medical complication; health care utilization